If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 47 = 7x + 7 Reorder the terms: 47 + 3x = 7x + 7 Reorder the terms: 47 + 3x = 7 + 7x Solving 47 + 3x = 7 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 47 + 3x + -7x = 7 + 7x + -7x Combine like terms: 3x + -7x = -4x 47 + -4x = 7 + 7x + -7x Combine like terms: 7x + -7x = 0 47 + -4x = 7 + 0 47 + -4x = 7 Add '-47' to each side of the equation. 47 + -47 + -4x = 7 + -47 Combine like terms: 47 + -47 = 0 0 + -4x = 7 + -47 -4x = 7 + -47 Combine like terms: 7 + -47 = -40 -4x = -40 Divide each side by '-4'. x = 10 Simplifying x = 10
| 5-8x=-7x+21 | | -5-8x=-7x | | 3x+4-2x=7x+3-5 | | 8x^2=24x | | 25x+17=5x-143 | | 9n^2+30n=-24 | | 3(5a^2-1)=6(a+2) | | -45x+68=84x-61 | | w^2-10w=-25 | | t^2-5t=40 | | 3X^2-24X=-4 | | 4x-7=7-3x | | 4-6k+k^2=0 | | r^2-6r+4=0 | | 21-x=-87-2x | | 6(x-2)=2(x+18) | | -5-7b=8b-6 | | 3s^2+4=4s+2s^2 | | log | | x-418.70=89.11 | | m^2-4m-66=0 | | .70x+.05(14-x)=.10(-32) | | 4x=92 | | 9(6+2a)=(2-4a) | | 0.81t=7.29 | | -8x-3=55 | | h=112t-16t^2 | | 15=y-19 | | x+9.7=16.1 | | 1-X+4X+17=-3X | | (2w-9)(1-w)=0 | | 5x^2=20x |